The Effect of Budget Management Participation and Budget Management Experience On Budget Performance: The Moderating Role Of SIMA SIPKD - Eliana; Farah Ivana; Banta Karollah; Naina Ursima (Universitas Pelita Harapan, 2024)
This study analyses the influence of budget management participation, and budget management experience, on budget performance and strengthened by SIMA SIPKD (IT). The sampling technique used is total sampling with the number of research samples to be analysed is the same as the population of 155 respondents, which are all members of the Aceh Government TAPA Team. The results showed that Budget Participation, and the experience of budget managers had a positive and significant effect on budget performance. SIMA SIPKD (IT) does not moderate the relationship between Budget Participation, budget manager experience and budget performance. The findings of this study agency problems in local budgeting are related to the experience of budget managers.